ISSUES THAT REQUIRE CREATIVE RESEARCH WHEN WORKING WITH GIFTED STUDENTS, IN THE FORMATION OF THEIR COGNITIVE ACTIVITY - Shakhista Sindarova Makhammatovna (Web of Journals Publishing, 2025)
This article is devoted to the stages of solving problems requiring creative research when working with gifted students, the formation of their educational activities.
Keywords: Attention, memory, speech, thinking, comparative qualifications, finding a similar one, hypothesis, creative abilities, reflection, knowledge, skills.